Strategi Menciptakan Sekolah Berkarakter di SDN 50 Singkawang - Alisa Alisa; Alya Nabila; Disvya Al Zikra; Nur Huda; Nur Safitri; Rifka Syahraini; Wita Priani; Monalisa Monalisa; Nurhayati Nurhayati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the strategy and implementation of character education at SDN 50 Singkawang as an effort to create a school with character. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that character education is implemented through various approaches, such as habituation of positive values, teacher role models, strengthening extracurricular activities, and active collaboration with parents. Schools accustom students to behave politely, disciplined, and responsibly through daily routines such as praying, maintaining cleanliness, and respecting each other. Teachers act as role models in every action, and parents are involved in supporting character values ​​at home. Despite facing challenges from diverse family backgrounds, the school has succeeded in creating a learning environment that supports the formation of student character. This study concludes that character education that is implemented consistently and collaboratively can produce a generation that is not only academically intelligent, but also morally and socially strong. Translated with DeepL.com (free version)